TECHNICAL VISUALIZATION AND ANIMATION IN TEACHING OF ENGINEERING SUBJECTS - DVOŘÁK, Karel; JEHLIČKA, Vladimír (Trends in education, 2013)
The deployment of computer applications for teaching of engineering design is addition to implementation of classical design procedures when creating 3D models of virtual prototypes and 2D drawings also possibility for creating visualizations. They serve to improve the aesthetic appearance of a virtual prototype, they are as well relevant for the interpretation of prototype functional properties. The paper introduces possibilities of carrying out technical visualizations and animations in engineering courses teaching. Focusing education on relevant issues helps to increase students' knowledge in the field of engineering design problems and to increase students' motivation for studying and professional life in a technical field.
Keywords: Digital model; Educational Project; Simulation; Visualization